Locally sourced supplementary feeding programs as a strategic intervention to address weight faltering in children: insights from a primary health center study - Haryani, Deby Aprilia; Amanda, Qorry; Sabjan, Novita (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2024)
Pemberian Makanan Tambahan (PMT), a supplementary food program using local ingredients, is a targeted intervention to address toddler malnutrition and weight faltering in Indonesia. Despite its widespread implementation, the long-term efficacy of the 14-day PMT program in sustaining growth recovery remains to be determined. This study aimed to evaluate the impact of a 14-day PMT intervention on weight gain and growth stability in children aged 6–59 months experiencing weight faltering. A prospective cohort study was conducted from May to August 2024 at Primary Health Center (Puskesmas) Ajibarang 1 in Banyumas, Central Java, Indonesia. The intervention consisted of 11 snacks and 3 main meals to meet 30–50% of daily caloric needs. Anthropometric measurements, including body weight (BW) and mid-upper arm circumference (MUAC), were collected pre- and post-intervention. 120 children participated, with baseline averages of 11.2 ± 1.5 kg for BW and 13.4 ± 1.7 cm for MUAC. Significant improvements were observed post-intervention, with averages of 12.9 ± 1.2 kg (BW) and 15.0 ± 1.4 cm (MUAC). A moderate positive correlation was identified between BW gain and MUAC (Spearman analysis). In conclusion, the PMT program effectively improves BW and MUAC in children at risk of growth faltering, highlighting its potential as a scalable intervention. These findings emphasize the importance of tailored nutritional programs during early childhood, a critical period for ensuring long-term health and developmental benefits. Advocacy and policy reforms are essential to support consistent implementation and global accessibility of nutritional interventions.